2021
DOI: 10.3389/fendo.2020.591837
|View full text |Cite
|
Sign up to set email alerts
|

Practical Clinical and Diagnostic Pathway for the Investigation of the Infertile Couple

Abstract: CapsuleThis expert opinion summarizes current knowledge on risk factors for infertility and identifies a practical clinical and diagnostic approach for the male and female partners of an infertile couple aimed to improve the investigation and management of fertility problems.BackgroundInfertility represents an important and growing health problem affecting up to 16% of couples worldwide. In most cases, male, female, or combined factor can be identified, and different causes or risk factors have been related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 109 publications
(119 reference statements)
1
17
0
3
Order By: Relevance
“…As related to the sperm parameters of subjects with primary infertility and those with secondary infertility, many studies reported large and overlapping differences, whereas this study showed no significant difference in sperm parameters in exception to the non-progressive sperm motility, which had a significant difference between the two types of infertility that agreed by other studies. The studied cases with primary type of infertility showed an increasing level of DNA fragmentation compared to other cases with a secondary type of infertility which are in agreement with similar studies and reported that the incidence of sperm DNA damage is higher in primary infertile patients who may harm fertility potential (Garolla, et al, 2021). All outcomes of involved cases and those with primary type infertility indicated a significant difference between the IgG and IgA detected by a direct method according to sperm tail bound.…”
Section: Discussionsupporting
confidence: 89%
“…As related to the sperm parameters of subjects with primary infertility and those with secondary infertility, many studies reported large and overlapping differences, whereas this study showed no significant difference in sperm parameters in exception to the non-progressive sperm motility, which had a significant difference between the two types of infertility that agreed by other studies. The studied cases with primary type of infertility showed an increasing level of DNA fragmentation compared to other cases with a secondary type of infertility which are in agreement with similar studies and reported that the incidence of sperm DNA damage is higher in primary infertile patients who may harm fertility potential (Garolla, et al, 2021). All outcomes of involved cases and those with primary type infertility indicated a significant difference between the IgG and IgA detected by a direct method according to sperm tail bound.…”
Section: Discussionsupporting
confidence: 89%
“…Conseguentemente, qualsiasi alterazione che interferisca con questi meccanismi può comportare dei problemi di fertilità. Un importante fattore da indagare nello studio della fertilità femminile è la riduzione di cicli ovulatori, dunque potenzialmente fertili, che caratterizza la PCOS [5]. La PCOS ha una prevalenza dell'8-13% nella popolazione femminile in età fertile e rappresenta la causa principale d'infertilità anovulatoria nelle donne [6].…”
Section: Fattori DI Rischio E Cause D'infertilità Femminileunclassified
“…As an important part of toxicology, toxicity to the female reproductive system is under intense scrutiny. Infertility affects approximately 16% of couples worldwide, 9 with female factors accounting for half of these cases. 10 The ovary is one of the most critical organs in the female reproductive system.…”
Section: Introductionmentioning
confidence: 99%